Understanding families' experiences following a diagnosis of non-syndromic craniosynostosis: a qualitative study. Issue 9 (24th September 2020) - Kuta, Victoria; Curry, Lauren; McNeely, Daniel; Walling, Simon; Chorney, Jill; Bezuhly, Michael
Abstract : Objectives: Craniosynostosis is typically diagnosed and surgically corrected within the first year of life. The diagnosis and surgical correction of the condition can be a very stressful experience for families. Despite this, there is little research exploring the impact that craniosynostosis has on families, especially in the period immediately following diagnosis and correction. In this study, the authors aimed to qualitatively examine the psychosocial experience of families with a child diagnosed with craniosynostosis. Design: Qualitative study. Setting: Tertiary care paediatric health centre. Participants: Mothers of children newly diagnosed with single-suture, non-syndromic craniosynostosis. Intervention: Semistructured interviews regarding parental experience with the initial diagnosis, their decision on corrective surgery for their child, the operative experience, the impact of craniosynostosis on the family and the challenges they encountered throughout their journey. Primary and secondary outcome measures: Thematic analysis, a type of qualitative analysis that provides an in-depth account of participant's experiences, was used to analyse the interview data. Results: Over a 4-year period, 12 families meeting eligibility criteria completed the study. Three main themes (six subthemes) emerged from the preoperative interviews: frustration with diagnostic delays (parental intuition and advocacy, hope for improved awareness), understanding what to expect (healthcare supports, interest in connecting with other families) and justifying the need for corrective surgery (influence of the surgeon, struggle with cosmetic indications). Two main themes (four subthemes) were drawn from the postoperative interviews: overcoming fear (the role of healthcare professionals, transition home) and relief (reduction in parental anxiety, cosmetic improvements). Conclusions: Overall, the diagnosis of craniosynostosis has a profound impact on families, leading them to face many struggles throughout their journey. A better understanding of these experiences will help to inform future practice, with a hope to improve this experience for other families moving forward.